Meal-time vs ad libitum feeding of finishing swine (feeder comparisons) - Vargas Vargas, J.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three feeding trials using 480 finishing pigs were conducted to evaluate meal time feeding versus ad libitum feeding. Growth rate and feed required per pound of gain were similar for all treatments. Carcass characteristics, except for backfat thickness, were similar for meal and ad libitum-fed pigs. Pigs fed ad libitum did have significantly more backfat (1.23 vs 1.01 inches) than the meal-fed pigs. Growth rate and feed efficiency were similar when rectangular feeders were compared with oval feeders for ad libitum feeding of finishing pigs.
Keywords: Swine; Meal-time vs. ad libitum; Finishing swine